Career Interests Among Young Adults of Minang Ethnicity in the Overseas of Lubuk Linggau City - Murisal Murisal; Widia Sri Ardias; Muhammad Zikri; Fadil Maiseptian (Universitas PGRI Yogyakarta, 2026)
This study examines the career interests of Minangkabau young adults living in Lubuk Linggau using the Social Cognitive Career Theory (SCCT) framework. A mixed-methods explanatory sequential design was conducted, starting with quantitative data from 78 members of the Minang Family Association assessed through Holland’s RIASEC model, followed by in-depth qualitative interviews. The findings show that the Realistic type dominates career interests, followed by Artistic, Enterprising, Investigative, Social, and Conventional. Qualitative results reveal that career preferences develop through early apprenticeship experiences, informal skill learning within the merantau tradition, and exposure to entrepreneurial role models in diaspora networks. Internal motivation and self-confidence interact with family expectations, educational pathways, and cultural values emphasizing resilience and independence in work. Theoretically, this study contributes to SCCT by demonstrating cultural migration practices shape self-efficacy and outcome expectations. Practically, the findings suggest the need for culturally responsive career guidance to support youth employability in diaspora contexts. Keywords: career interest, riasec model, social cognitive career theory